Analisis kontribusi dan efektivitas pajak reklame di Kota Jambi - Puspita Sari, Widi; Nurjanah, Rahma; Hardiani, Hardiani (Jurnal Paradigma Ekonomika, 2024)
This research aims: (1) To analyze the development of Advertisement Tax in Jambi City in 2010 - 2022. (2) To analyze how big the contribution of Advertisement Tax is to Jambi City's Regional Original Income in 2010 - 2022. (3) To analyze the effectiveness of Advertisement Tax in Jambi City 2010 - 2022. (4) To analyze the potential of Jambi City Advertising Tax based on Klassen Typology for 2010 - 2022. This research uses secondary data with time series data for the period 2010 - 2022. The method used in this research is descriptive qualitative.  The research results provide results (1) The development of Jambi City Advertisement Tax during 2010 - 2022 is an average of 8.60 percent. (2) The contribution of advertising tax to Jambi City's original regional income for 2010 - 2022 is an average of 4.48 percent. (3) The effectiveness of advertising tax in Jambi City in 2010 - 2022 is an average of 90.08 percent. (4) Potential analysis based on the class typology of Jambi City advertisement tax for 2010 - 2022, the average proportion is 0.05 percent and the average growth is 0.88 percent. The potential income for Jambi City Advertisement Tax is included in the back category.